Effect of aging on discoloration of two composite surface sealants - Kianvash Rad, Niloofar; Javid, Bahar; Torabzadeh, Hasan; Ghahari, Arezoo (Journal of Dental School, 2019)
Objectives Composite surface sealants were introduced aiming to prevent or decrease the discoloration and microleakage of composite restorations. This study sought to assess the effect of aging on discoloration of two composite surface sealants. Methods In this experimental study, 24 samples were fabricated of Fortify Plus and BisCover LV composite surface sealants (10 mm in diameter and 1 mm in thickness) and their baseline color coordinates were measured using the CIE L* a* b* system by a reflection spectrophotometer. The samples made of each material (n = 12) were randomly divided into 4 groups of 3 and aged in xenon chamber, tea, distilled water and dry ambient environment (control). Color change (ΔE*) was calculated in the reflectance mode. The data were analyzed using two-way ANOVA and t-test (P < 0.05). Results The minimum ∆E* value was 0.95 ± 0.6 belonging to Fortify Plus stored in the dry ambient environment while the maximum ∆E* value was 21.85 ± 4 belonging to BisCover LV aged in tea. Two-way ANOVA showed significant differences in ∆E* among the aging protocols (P < 0.001); the effect of two materials (P < 0.001) and the interaction effect of the type of material and aging were also significant (P = 0.001). Conclusions It can be concluded that aging affects the discoloration of composite surface sealants. Tea caused the greatest discoloration. There were no significant differences in the color change of the two materials after accelerated aging with xenon.